Sosialisasi Web PhET Simulation sebagai media Virtual Lab di Sekolah Dasar - Puji Rahayu; Fitri Nuraeni; Anisa Putri Ananda; Dewi Wahyuningsih; Dinda Nur Azizah; Indri Indriani; Puspita Hardaningtyas (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
This seminar activity aims to introduce the PhET application as a teaching medium that can be used in learning activities in elementary schools. PhET (Physics Education Technology) is a site that provides learning simulations physics which can be downloaded for free for the benefit of learning in class or for individual learning interests. By using PhET simulation, students are expected to be able to better understand the theory and practicum that has been carried out into the simulation. From the results of the questionnaire and the satisfaction that was filled in by the seminar participants, it can be seen that 86% of the messages from the subjects present did not know about this PhET application before and the other 24% knew but had never used it. As a result of this seminar activity, the subjects who attended the seminar activities understood and were able to apply PhET simulations to learning activities